Isolation of curcumin compounds in Temulawak Rhizome (Xanthorrhiza Roxb) - Ramandha, Muhammad Eka Putra; Kresnapati, I Nyoman Bagus Aji (Journal of Natural Sciences and Mathematics Research, 2023)
The curcumin compounds in Temulawak Rhizome have been isolated and identified.. This study aims to identify curcumin compounds in temulawak rhizome by modifying methods that pay attention to the efficiency of funds and the use of materials. In general, the method of isolation and identification is carried out. The methods used are (1) Extraction, (2) Thin Layer Chromatography, (3) Column Chromatography and (4) Infrared (IR) Testing. Based on comparing the sample's Retention Factor (RF) value with the standard curcumin compound, the results were identical, and the positive sample contained a curcumin compound. The results of the Infrared spectrum can be assumed that the sample is a flavanols group, which can be seen from the wavelength range of identical functional groups in curcumin compounds.